2014
DOI: 10.1089/jwh.2013.4653
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Women and Men with Intermittent Claudication: A Cross-Sectional Study

Abstract: Women claudicants have higher risk factors and more frequent cardiovascular comorbidity than men do. Women have a lower capacity for exercise and a poorer quality of life than male claudicants, despite having a similar ABI. These poorer outcomes in women can be partially explained by the presence of greater osteoarticular comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…18 Interestingly, previous research suggested lower baseline WIQ scores in women. 27 These baseline gender differences were not observed in the present study. The magnitude of change in women's total WIQ score after 12 months of SET also did not differ from that of men.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…18 Interestingly, previous research suggested lower baseline WIQ scores in women. 27 These baseline gender differences were not observed in the present study. The magnitude of change in women's total WIQ score after 12 months of SET also did not differ from that of men.…”
Section: Discussioncontrasting
confidence: 65%
“…A higher prevalence of comorbidities and advanced female age in previous research could explain these opposing results as these factors have influence on WIQ scores. 27 On the other hand, we observed lower walking ability scores in various subdomains for women, most strikingly with regard to walking speed. Previous studies also reported that women with IC ambulate slower in a community setting.…”
Section: Discussionmentioning
confidence: 58%
“…To the best of our knowledge, the available literature on the response of women to rehabilitation in PAD is poor, and the present results represent a novel report. The only confirmation of previous data 10,37 is the low walking performance of women compared to that of men in absolute terms. The functional capacity at entrance to the program measured with both treadmill and ground-walking tests was lower in the female population with the same hemodynamic condition.…”
Section: Discussionmentioning
confidence: 48%
“…This aspect may refer to the lower aerobic efficiency typical of the female sex or the lower biomechanical efficiency aggravated by deconditioning, possibly related to the presence of comorbidities. 37,38 In daily activities, women move at a slower rate than men and present a different ambulatory pattern. 39 However, after rehabilitation, the same degree of functional improvement, which was the main focus of our study, was observed in the two subpopulations, with an average variation in exercise capacity between 20% and 110% for patients of both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation